Pengaruh Lingkungan, Perilaku, Struktur Organisasi dan Implementasi Sistem Informasi Berbasis Komputer terhadap Kinerja Karyawan Pemerintah Kabupaten Sorong, Papua - Suaib, Muhammad Ridha (Jurnal Aplikasi Manajemen, 2008)
Objectives of the research are to analyze the influence of environment, behavior, organizational structure and implementation of computer based-informational system variables over the civil servant performance, and to analyze the indicator of computer based-informational system implementation that has dominant influence over the civil servant performance. Populations in this research are employees or information from Department, Body, Office and Division on the Local Secretariat Office at Sorong Regency, Papua. Techniques of sample collecting in this research use a Model Census and multiple-linear regression analysis, and the hypothesis is tested using F-test and t-test on the trustworthy level of 95% (a = 5%). The testing hypothesis I was tested by the value of F. (77.218) is higher that F (2.51). Hypothesis II is tested in which the indicator that having dominant influence over the civil servant performance is the indicator of easiness in completing the jobs that having significant and the highest value of regression coefficient.